2007
DOI: 10.19030/tlc.v4i9.1549
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Students Predispositions Toward Communication, Learning Styles, And Sex On Academic Achievement

Abstract: Females are more apprehensive when talking in class, but more nonverbally immediate, and prefer a collaborative learning style. Males prefer independent and avoidant learning styles, and report learning less than females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, the importance of Omani students’ high behavioural intention to share and exchange knowledge is clarified. Managers and staff members characterised by a positive attitude and subjective norms (So and Bolloju, 2005; Jolaee et al , 2014) inspire students to share knowledge (Allen et al , 2007; Liu et al , 2013; Naser et al , 2016b). Abili et al (2011) determined a strong relationship among managers, staff and students’ subjective norms and knowledge-sharing intention.…”
Section: Construct Development and Literature Reviewmentioning
confidence: 99%
“…Accordingly, the importance of Omani students’ high behavioural intention to share and exchange knowledge is clarified. Managers and staff members characterised by a positive attitude and subjective norms (So and Bolloju, 2005; Jolaee et al , 2014) inspire students to share knowledge (Allen et al , 2007; Liu et al , 2013; Naser et al , 2016b). Abili et al (2011) determined a strong relationship among managers, staff and students’ subjective norms and knowledge-sharing intention.…”
Section: Construct Development and Literature Reviewmentioning
confidence: 99%
“…Previous research has revealed a significant relationship CA and learning preferences using participants from high school and collegiate settings (Allen et al, 2007; Andersen & Bell-Daquilante, 1980; Bourhis & Berquist, 1990; Bourhis & Stubbs, 1991; Dwyer, 1998; Johnson, 2003). This study sought to extend this body of research by testing whether a similar relationship exists between CA and learning preferences in an organizational setting.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Three extant studies have examined how CA influences learning style preferences (Allen et al, 2007; Bourhis & Stubbs, 1991; Dwyer, 1998). Two of these studies used the Grasha-Reichmann Student Style Scale (see Reichmann & Grasha, 1974) to assess undergraduate students’ inclination for six learning styles: independent, dependent, avoidant, participative, collaborative, and competitive.…”
Section: Theoretical Rationalementioning
confidence: 99%
See 2 more Smart Citations